Laboratory Investigation of Reclaimed Asphalt Mixtures Containing Cyclogen and Vacuum Bottom Rejuvenators. (17th January 2023) - Ziari, Hassan; Mojaradi, Barat; Saadatjoo, Seyed Amir; Amini, Amir; Najafi Moghaddam Gilani, Vahid; Hosseinian, Seyed Mohsen
Abstract : The use of reclaimed asphalt pavement (RAP) to create recycled asphalt mixture is attracting great interest because of landfill space decrease and natural resources saving. Also, incorporating rejuvenators is an effective method to promote the utilization of RAP materials in hot mix asphalt (HMA) production. The main goal of this study was to evaluate the effect of Cyclogen and vacuum bottom (VB) rejuvenators on the performance of RAP mixtures against moisture sensitivity, rutting resistance, and tensile strength. In this regard, mixtures were constructed with different RAP contents (0, 35, and 70% by asphalt mix weight) and virgin aggregates. Furthermore, three contents of Cyclogen (0, 5, and 10%) and VB (0, 15, and 30%) by the weight of RAP binder were used. The laboratory test results revealed that RAP materials enhanced the indirect tensile strength, rutting resistance, and moisture sensitivity of asphalt samples. Moreover, increasing RAP content improved the rutting resistance and permanent deformations of asphalt samples. The addition of RAP also enhanced the resilient modulus and tensile strength of asphalt samples; this increase was subject to RAP content applied. Furthermore, the effect of rejuvenators on the performance characteristics of RAP mixtures showed that adding VB and Cyclogen decreased tensile strength, resilient modulus, and strain creep and increased the moisture sensitivity of RAP mixtures.